Investment-cash flow sensitivity cannot be a good measure of financial constraints: Evidence from the time series - Chen, Huafeng (Jason); Chen, Shaojun (Jenny) (Journal of Financial Economics, 2012)
Investment-cash flow sensitivity has declined and disappeared, even during the 2007–2009 credit crunch. If one believes that financial constraints have not disappeared, then investment-cash flow sensitivity cannot be a good measure of financial constraints. The decline and disappearance are robust to considerations of R&D and cash reserves, and across groups of firms. The information content in cash flow regarding investment opportunities has declined, but measurement error in Tobin's q does not completely explain the patterns in investment-cash flow sensitivity. The decline and disappearance cannot be explained by changes in sample composition, corporate governance, or market power—and remain a puzzle.